Mommies' girls get dresses, daddies' boys get toys: Gender preferences in Poland and their Implications - Krzysztof Karbownik; Michał Myck (Uppsala University, Department of Economics, 2011)
We examine the relationship of child gender with family and economic outcomes using a large dataset from the Polish Household Budgets' Survey (PHBS) for years 2003-2009. Apart from studying the effects of gender on family stability, fertility and mothers' labor market outcomes, we take advantage of the PHBS' detailed expenditure module to examine effects of gender on consumption patterns. We find that a first born daughter is significantly less likely to be living with her father compared to a first born son and that the probability of having the second child is negatively correlated with a first born daughter. Using the context of the collective model we provide interpretation of these results from the perspective of individual parental gender preferences. We also examine the potential effects of sample selection bias which may affect the results and may be important for other findings in the literature. Labor supply of mothers and overall child-related consumption is not affected by gender of the first child, but the pattern of expenditure significantly varies between those with first born sons and first born daughters. One possible interpretation of the findings is that Polish fathers have preferences for sons and Polish mothers have preferences for daughters. Expenditure patterns suggest potential early determination of gender roles - mommies' girls get dresses and daddies' boys get toys.
urn:nbn:se:uu:diva-164949
Keywords: J12; J13; J16; 330; gender preferences; child outcomes; fertility; Familienökonomik; Kinder; Geschlecht; Konsumentenverhalten; Polen